2005
DOI: 10.1089/jwh.2005.14.808
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual and Reproductive Factors and Fracture Risk: The Leisure World Cohort Study

Abstract: The estrogen-related events of menarche, pregnancy, and menopause were not associated with osteoporotic fracture risk in a consistent manner. Other factors related to these events may be influencing development of osteoporosis and the likelihood of sustaining a fracture in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 79 publications
(107 reference statements)
4
41
2
Order By: Relevance
“…Age at the last menstrual period was not a statistically significant predictor of hip fracture in the fully adjusted model (Table 3). This agrees with several earlier studies showing no statistically significant association between age at menopause and hip fracture risk [19,21,29,42]; however, age at the last menstrual period appeared to modify the association between parity and hip fracture risk. Women with three or more births and aged over 50 on the (Table 4).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Age at the last menstrual period was not a statistically significant predictor of hip fracture in the fully adjusted model (Table 3). This agrees with several earlier studies showing no statistically significant association between age at menopause and hip fracture risk [19,21,29,42]; however, age at the last menstrual period appeared to modify the association between parity and hip fracture risk. Women with three or more births and aged over 50 on the (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…Also, similar to earlier studies [15,19], we found that parity appears to be protective against hip fractures even according to models adjusted for BMI. Pregnancy can have favorable effects on bone size and geometry and therefore reduce the long-term fracture risk [40,41].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data are thus compatible with the notion that the time of menarche is inversely related to the risk of vertebral and nonvertebral fragility fractures, independent of the aging process. (8)(9)(10)(11) Both pubertal timing (39) and peak bone mass (40,41) are under the strong influence of hereditable factors and can be moderately affected by common environmental determinants. (42) The hereditable component of pubertal timing was well identified by both twin (43)(44)(45)(46)(47) and mother-daughter relationship (48)(49)(50)(51)(52) studies.…”
Section: Discussionmentioning
confidence: 99%
“…(4)(5)(6)(7) These findings are supported by observations that late pubertal maturation is linked to an increased risk of vertebral and nonvertebral fragility fractures. (8)(9)(10)(11) Retrospective epidemiological studies have shown that the inverse relationship between bone mineral mass or density and age of menarche seen in premenopausal women has generally been ascribed to the duration of sex hormone exposure up to the time of peak bone mass. (2,(12)(13)(14) These findings imply that, the longer the duration of sex hormone exposure, the higher peak bone mass will reach.…”
mentioning
confidence: 99%